Learning at school and outside. Comparing interactive styles in a community of Tapajós (Pará, Brazil) - Medaets, Chantal (RUNA, archivo para las ciencias del hombre, 2019)
In this paper I compare learning modalities and codes of conduct that govern relations outside the school space, in the daily interactions of a community in the Lower Tapajós region, and those that occur within the school. Are transmission and learning practices in the community and family life the same or do they inform those mobilized in the school setting? The preliminary results indicate that there are significant differences in the patterns of interaction in both spaces and that teachers and students seem to shift from one pattern to the other without demonstrating conflicts.